2016
DOI: 10.1016/j.celrep.2016.08.085
|View full text |Cite
|
Sign up to set email alerts
|

Uniformity of Peptide Release Is Maintained by Methylation of Release Factors

Abstract: SUMMARY Termination of protein synthesis on the ribosome is catalyzed by release factors (RFs), which share a conserved glycine-glycine-glutamine (GGQ) motif. The glutamine residue is methylated in vivo, but a mechanistic understanding of its contribution to hydrolysis is lacking. Here we show that the modification, apart from increasing the overall rate of termination on all dipeptides, substantially increases the rate of peptide release on a subset of amino acids. In the presence of unmethylated RFs, we meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
78
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(89 citation statements)
references
References 38 publications
10
78
1
Order By: Relevance
“…We performed the same analysis of stop codon-aligned ribosome footprints with data from Δefp cells (Woolstenhulme et al, 2015) and found no evidence that the loss of EFP enhances pausing at stop codons (Figure 7A). Additionally, recent biochemical work using an E. coli in vitro reconstituted translation system has shown that EFP does not stimulate the rate of release of fMet-Pro or fMet-Gly from tRNA by RF1 or RF2 (Pierson et al, 2016). These data argue that the function of eIF5A in translation termination is unique to eIF5A.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We performed the same analysis of stop codon-aligned ribosome footprints with data from Δefp cells (Woolstenhulme et al, 2015) and found no evidence that the loss of EFP enhances pausing at stop codons (Figure 7A). Additionally, recent biochemical work using an E. coli in vitro reconstituted translation system has shown that EFP does not stimulate the rate of release of fMet-Pro or fMet-Gly from tRNA by RF1 or RF2 (Pierson et al, 2016). These data argue that the function of eIF5A in translation termination is unique to eIF5A.…”
Section: Resultsmentioning
confidence: 99%
“…We also showed in vitro that eIF5A stimulates eRF1-mediated peptide release by 17-fold (Figure 6) and that this enhanced rate functions through canonical GGQ-hydrolysis (Figure S7C). In contrast to eIF5A, EFP was shown to have no function in RF1- or RF2-mediated peptidyl hydrolysis (Pierson et al, 2016). These observations support a model where eIF5A functions globally to stimulate slow reactions at the ribosomal peptidyl transferase center (PTC) while EFP is more specialized for several specific slow peptide motifs.…”
Section: Discussionmentioning
confidence: 99%
“…The variability across taxonomy of the bias for proline also suggests that translation termination stalling at C-terminal proline could be species specific. In this regard, an in vitro study of the release factor (RF)-mediated rates of peptide release has suggested that peptide release is particularly inefficient on peptides terminating with proline or glycine, for both RF1 and RF2, and especially in the absence of methylated RFs factors (44). The addition of elongation factor P (EF-P) had no effect on the release rate suggesting that EF-P does not significantly promote peptide release on proline and glycine residues (44).…”
Section: Discussionmentioning
confidence: 99%
“…The catalytic GGQ motif inserts into the 50S peptidyl-transferase center (PTC) adjacent to the CCA end of P-tRNA. Ribosomes retain the non-rotated conformation in RF-bound structures, including those with mutated or post-translationally modified RFs (Pierson et al, 2016;Santos et al, 2013;Zeng and Jin, 2018) or when RFs are perturbed by the termination inhibitor blasticidin S (Svidritskiy and Korostelev, 2018a, b) or by a sense codon in the A site (Svidritskiy et al, 2018). The catalytic GGQ loop adopts the same compact conformation comprising a short α-helix in pre-hydrolysislike and post-hydrolysis structures, as discussed below.…”
Section: Introductionmentioning
confidence: 98%